Hall numbers of some complete k-partite graphs - Allagan, Julian A. (Utilitas Mathematica, 2012)
The Hall number is a graph parameter closely related to the choice number. Here it is shown that the Hall numbers of the complete multipartite graphs K(m,2,...,2), m ≥ 2, are equal to their choice numbers.